Asymmetric synthesis of (+)-teratosphaerone B, its non-natural analogue and (+)-xylarenone using an ene- and naphthol reductase cascade. Issue 37 (12th September 2022) - Manna, Tanaya; De, Arijit; Nurjamal, Khondekar; Husain, Syed Masood
Abstract : Bienzyme cascade reduction of putative biosynthetic naphthoquinone substrates give easy access to natural naphthalenones with high yields and high stereoselectivity. Abstract : Herein, a one-pot bienzymatic cascade containing an ene and a naphthol reductase is developed. It is applied for the synthesis of (+)-(3 R, 4 R )-teratosphaerone B, its non-natural regioisomer in both cis - and trans -forms and (+)-xylarenone by the reduction of chemically synthesized naphthoquinone precursors in high yields (76–92%) and excellent ee (>99%). This work implies similar biosynthetic steps in the formation of the synthesized natural products.